Measuring Large Non‐planar Optics: Interferometric measurement of large‐scale cylindrical optical components. Issue 5 (17th December 2015) - Richters, Jan‐Peter; Wolfgramm, Florian; Schuhmann, Rainer
Abstract: The evaluation of the surface form quality of large‐scale optical components in general and large cylindrical components in particular is most challenging. Such surfaces can be measured with planar Fizeau‐type interferometers equipped with computer generated holograms. This article provides an overview of the measurement process using sub‐aperture stitching techniques, the degrees of freedom of the measuring system, the requirements on input data and the importance of error‐corrected holograms.